Volatilitas Kebijakan dan Tantangan Normatif: Keterlibatan Amerika Serikat di Suriah (2011–2024) dan Rekonfigurasi Tata Kelola Global - Wajid Fauzi; Ida Rochani Adi; Hindun Hindun (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The Syrian conflict, ongoing since 2011, has revealed the volatility of American foreign policy and raised critical normative questions for global governance. This article examines the trajectory of U.S. engagement in Syria from 2011 to 2024, emphasizing the dynamic interplay between evolving policy strategies and international norms. Utilizing a qualitative case study design that combines document analysis and process tracing, the study identifies three major phases: Obama’s ambivalent interventionism, Trump’s pragmatic retrenchment, and Biden’s selective return to multilateralism. The findings demonstrate that domestic political polarization, geopolitical rivalries involving Russia, Iran, and Turkey, and normative tensions surrounding sovereignty and humanitarian protection collectively shaped U.S. policy volatility. These oscillations undermined America’s credibility as a consistent norm entrepreneur, contributing to the erosion of unipolar governance structures. Consequently, the Syrian conflict has accelerated a transition toward multipolar and fragmented global governance, in which non-Western powers and non-state actors increasingly influence outcomes. The article argues that addressing policy volatility and normative fragmentation requires deeper engagement with regional powers and non-state actors while reinforcing multilateral frameworks to manage protracted crises in an era of multipolarity.